The effect of integration between biochar and mineral fertilization on wheat yield and protein content in seeds - زيدان علي; جزدان عمر ابراهيم; حيدر علي (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out at (ACSAD) research station in the Khirbet al-Tin area - Homs Governorate, and is a field experiment consisting of (12) treatments, resulting from the overlap between three levels (0, 1/2 and 1) of the fertilizer formula adopted for wheat crop, and four levels of biochar of olive mill residues (0, 1, 2 and 4%), based on the weight of the soil, in the surface layer with a depth of (15 cm), where it was sown with durum wheat seeds, variety (ACSAD 1105), the harvest took place in June 2020. The yield production of grains and protein content, were estimated, then the Fertilizer Use Efficiency (FUE), and (Biochar Productivity Efficiency (BPE) were calculated. The results showed that the individual additions according to the stated levels of the mineral fertilizers and the biochar, led to an increase in the grain yield and protein content with a high degree of significance (***). Also, (FUE) in terms of seeds production (kg seeds/kg fert), increased significantly with the increase in the levels of biochar about (79.7%) at (F1) level, and (19.2 or 4.4%), at (F2) level of miniral fertilization. (BPE) also, achieved an extra yield of (0.366 - 1.1 tons h-1) in presence of the mineral fertilization at (F1 and F2) levels, comparative with the control (F0 B0).